Archiving Television and Celebrating Legacy. Mike Bongiorno’s Centenary Exhibition and TV Miniseries - Cardini, Daniela (Unlocking Television Archives in the Digital Era. 16th Media Mutations International Conference, 2026)
This paper will focus on the exhibition “Mike Bongiorno 1924-2024” (Palazzo Reale, Milan, Sept. 17th-Nov. 17th, 2024) and on the TV miniseries Mike (Rai Uno, 2024), both of them produced to commemorate the centenary of birth of Mike Bongiorno, a pivotal figure in Italian television history. The present contribution aims to analyze the mechanisms through which TV products are preserved, exhibited, and historicized by TV institutions. The exhibition, curated by the Fondazione Mike Bongiorno, highlights the role of television archives in shaping media memory, institutional legitimacy, and cultural heritage. The miniseries Mike (Rai Uno, 2024) is focused on Mike Bongiorno’s personal life from his very beginnings in Rai public service, from the mid-Fifties to the Seventies, to his shift to Fininvest/Mediaset commercial television in 1980. The paper compares the archival and historiographical approaches of both projects, situating them within the broader frameworks of television studies, celebrity studies and production studies.